Digitalisation Of Sukamandi Hulu Village Through The Creation Of An Information System Application Web-Based Population Data To Support The Concept Of Smart Government - Rosmaini, Elly; Nasution, Putri Kahiriah; Zendrato, Niskarto; Putri, Mimmy Sari Syah (Talenta Publisher, 2023)
The lack of effectiveness in the process of recording, searching and reporting population data using manual methods makes many obstacles in the activity. Population Registration is an activity routinely carried out by the government for science related to techniques, collection, recording, population data consisting of moving data, migrant data, birth data, death data. This Population Data Recording Application is designed in such a way as to facilitate data recording and report generation efficiently and effectively. This application is built with Flowchart notation, Data Flow Diagram, Entity Relationship Diagram and programming is PHP and MySql as DBMS, with engineering development methods and system modelling, needs analysis, design, coding, testing and maintenance. The Population Data Recording Application has several advantages, including being able to display the number of residents in Sukamandi Hulu Village from each month.